Placement of Mobile Base Stations in Wireless Sensor Networks using Vector Dominating Set - K, Pradeepa; Santhana Krishna (INFOCOMP Journal of Computer Science, 2021)
Abstract: Numerous research works has focused on the positioning multiple mobile sinks in the network area to improvise the lifetime of wireless sensor network. The experimental results of the research works clearly indicates that the lifetime of the network will be increased several folds on exploiting multiple mobile sinks in the network rather than static sinks. The proposed paper employs multiple mobile sinks to increase the lifetime of network. The research work focuses on finding the best energy rich locations for placing multiple mobile sinks in a way it delays the expiry of one hop sensor nodes. The paper contributes an Integer Linear Programming (ILP) formulation for the positioning of mobile sinks. In an attempt to find the best location to place the mobile sinks, the paper discretizes the solution space as a replacement for the entire network. The energy rich positions for positioning the mobile sinks are found through the solution of the ILP formulation. As an alternative of running the ILP on a continuous search space, the solution space is discretized and ILP is implemented on the discretized space. Experimental results indicate that the proposed ILP model maximizes the network lifetime to a great extent in comparison with the static sink method.